Yield of atrial fibrillation detection with Textile Wearable Holter from the acute phase of stroke: Pilot study of Crypto-AF registry. (15th January 2018) - Pagola, Jorge; Juega, Jesus; Francisco-Pascual, Jaume; Moya, Angel; Sanchis, Mireia; Bustamante, Alejandro; Penalba, Anna; Usero, Maria; Cortijo, Elisa; Arenillas, Juan F.; Calleja, Ana I.; Sandin-Fuentes, Maria; et al.
Abstract: Background: We describe the feasibility of monitoring with a Textile Wearable Holter (TWH) in patients included in Crypto AF registry. Methods: We monitored cryptogenic stroke patients from stroke onset (< 3 days) continuously during 28 days. We employed a TWH composed by a garment and a recorder. We compared two garments (Lead and Vest) to assess rate of undiagnosed Atrial Fibrillation (AF) detection, monitoring compliance, comfortability (1 to 5 points), skin lesions, and time analyzed. We describe the timing of AF detection in three periods (0–3, 4–15 and 16–28 days). Results: The rate of undiagnosed AF detection with TWH was 21.9% (32 out of 146 patients who completed the monitoring). Global time compliance was 90% of the time expected (583/644 h). The level of comfortability was 4 points (IQR 3–5). We detected reversible skin lesions in 5.47% (8/146). The comfortability was similar but time compliance (in hours) was longer in Vest group 591 (IQR [521–639]) vs. Lead 566 (IQR [397–620]) (p = 0.025). Also, time analyzed was more prolonged in Vest group 497 (IQR [419–557]) vs. Lead (336 h (IQR [140–520]) (p = 0.001)). The incidence of AF increases from 5.6% (at 3 days) to 17.5% (at 15th day) and up to 20.9% (at 28th day). The percentage of AF episodes detected only in each period was 12.5% (0–3 days); 21.7% (4–15 days) and 19% (16–28 days). Conclusions: 28 days Holter monitoring from the acute phase of the stroke was feasible with TWH. Following our protocol, only five patients were needed to screen to detected one case of AF.